Effect of shearing speed on the shear strength parameters of remoulded lateritic soil / Mohideen Abdul Kader Abdul Hamid - Abdul Hamid, Mohideen Abdul Kader (1996)
Shearing speed or rate of loading applied during the triaxial test normally is being practised on the basis of the value recommended by the British Standard on soil testing. The value recommended is based on the consolidation time for a particular soil. Shearing speed that is being widely practised represent the recommendation given based on the testing done on non-Malaysian soils. However, for Malaysian soils, the behaviour may not necessarily be the same. In fact, some engineers have questioned on the validity of recommended speed and have asked for a much slower speed. From the study there was no significant changes in shear strength parameters due to variation in shearing speed of the laterite soil. The shearing speed might affect the effective stress since the equalisation of pore water pressure depends on the rate of shearing applied. In terms of deviator stress the effect of shearing speed can be omitted as the pore water pressure is the same for both total and effective stresses. The increase in pore water pressure with time might have a considerable changes for different rate of speed. The study also concluded that as far as the lateritic soil is concerned, the shearing time for CIU could be faster i.e. less than 2 hours as recommended by BS. This being supported from the results of the shear strength parameters.